From Cultural Symbol to Campus “Idol” and Back - Sheri A. Lullo (Asian Studies)
A sculpture known as “The Idol” was, until the summer of 2021, prominently displayed on the campus of Union College in Schenectady, New York. Since the late 19th century, this sculpture had been coated with countless layers of paint by rival student groups as part of yearly campus rituals. Few in the community were fully aware, however, that the work is a venerable stone guardian lion from late imperial China, which was gifted to the college by an alumnus in 1874. The stone lion may be considered as an “orphaned object” in at least three ways. First, there is no official documentation of its excavation, provenance or transfer to the United States. Second, it is a singular fragment of an original pair—Union College possesses the “female” lion of the customary male-female dyad of stone guardian lions from Chinese tradition. And finally, veiled and rendered amorphous by an ever thicker coating of paint for over a century, the work’s agency as a guardian and Chinese cultural symbol was denied as it was reimagined through rituals that served to mediate student identities. This paper will explore the rich life history and changing agency of Union College’s Chinese stone lion within the context of the introduction of Chinese art to the United States in the late 19th and early 20th centuries.